1990
DOI: 10.1111/j.1476-5381.1990.tb12074.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen induces leucopenia in non‐immunised guinea‐pigs injected with platelets from actively sensitized animals

Abstract: Ovalbumin administration to animals injected with 0.5–5 × 106 washed platelets μl−1 from actively sensitized animals induced a marked decrease (maximum of around 50% at 60 min) in the number of circulating leucocytes, whereas platelet counts were unaffected. The intensity of the decrease in leucocyte counts was dependent upon the concentration of the injected platelets. No drop in leucocyte counts was measured upon antigen challenge of guinea‐pigs injected with platelets from non‐sensitized animals. This pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1991
1991
1995
1995

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…Previous work has suggested an important role for lipoxygenase products as the platelet-dependent leucopenia was inhibited by the mixed lipoxygenase inhibitor BW755C but not indomethacin (Pretolani et al, 1990). In the present series of experiments however, we failed to support a role for lipoxygenase products in this response, as the selective lioxygenase inhibitor BWA4C (Tateson et al, 1988) was ineffective at a concentration previously demonstrated to inhibit the 'leukotriene-dependent' component of bronchial anaphylaxis in the guinea-pig (Payne et al, 1988).…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Previous work has suggested an important role for lipoxygenase products as the platelet-dependent leucopenia was inhibited by the mixed lipoxygenase inhibitor BW755C but not indomethacin (Pretolani et al, 1990). In the present series of experiments however, we failed to support a role for lipoxygenase products in this response, as the selective lioxygenase inhibitor BWA4C (Tateson et al, 1988) was ineffective at a concentration previously demonstrated to inhibit the 'leukotriene-dependent' component of bronchial anaphylaxis in the guinea-pig (Payne et al, 1988).…”
Section: Discussioncontrasting
confidence: 87%
“…However, it is unlikely that inhibition of the cyclooxygenase pathway of arachidonic acid metabolism or inhibition of PAF generation is responsible for the efficacy of cetirizine as it has previously been demonstrated that indomethacin and the selective PAF antagonist, WEB 2086, were ineffective in inhibiting the antigen-dependent leucopenia (Pretolani et al, 1990). Cetirizine has also been reported to inhibit the accumulation of leucocytes in the skin of allergic individuals following antigen challenge in vivo (Fadel et al, 1987;Charlesworth et al, 1988;Michel et al, 1988;Henocq & Rihoux, 1990) and will inhibit both PAF and FMLPinduced chemotaxis of human eosinophils in vitro (De Vos et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations